Evaluasi Non-Tes Sebagai Instrumen Pengembangan Karakter Dan Keterampilan Abad 21 - Ashma Rohimah, Siti; Mutmainnah; Khoeriyah, Siti Fatonah; Baskara Putri, Maharanie; Najmudin, Dudun (Universitas Sulawesi Barat, 2025)
Non-test evaluation is an alternative approach in assessing learning processes and outcomes that cannot be optimally measured through written tests. In the midst of the demands of 21st century education that emphasizes the development of character and skills such as critical thinking, collaboration, communication, and creativity, non-test evaluation comes as a relevant and adaptive instrument. This study aims to explore the effectiveness of non-test evaluation as an instrument in developing 21st century character and skills in learners. Non-test evaluation, which includes observation, self-assessment, portfolio, and project assessment, is believed to provide a more holistic picture of student development compared to written tests. The research method used was a literature study and comparative analysis of various evaluation approaches. The results show that non-test evaluation is able to measure affective and psychomotor aspects that are difficult to access through written tests, thus supporting character development such as cooperation, responsibility, and 21st century skills such as critical thinking and problem solving. Therefore, the application of non-test evaluation in learning activities is strongly recommended to realize a comprehensive education system that is in accordance with the real-life context.